2023
DOI: 10.1186/s12885-023-10636-5
|View full text |Cite
|
Sign up to set email alerts
|

The hsa_circ_0000276-ceRNA regulatory network and immune infiltration in cervical cancer

Abstract: Background Our previous studies have confirmed that miR-154-5p can regulate pRb expression, and thus, play a tumor suppressor role in HPV16 E7-induced cervical cancer. However, its upstream molecules have not been elucidated in the progression of cervical cancer. This study aimed to explore the role of the miR-154-5p upstream molecule, hsa_circ_0000276 in cervical cancer development and its possible mechanisms of action. Methods We detected differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Based on these findings, circ_0000276 may contribute to cervical cancer development and progression by modulating immune infiltration. 86…”
Section: Cervical Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…Based on these findings, circ_0000276 may contribute to cervical cancer development and progression by modulating immune infiltration. 86…”
Section: Cervical Cancermentioning
confidence: 99%
“…The results showed that knockdown of the circ_0000276 resulted in significant inhibitions in cell proliferation. 86 Furthermore, it was found that silencing of circ_0000276 resulted in a higher number of malignant cells being arrested in the G1 phase of the cell cycle, whereas there was a decrease in malignant cells in the S phase. 86 Similarly, the suppression of circ_0000276 resulted in a notable rise in the apoptosis rate of cells, suggesting that circ_0000276 within F I G U R E 2 A schematic representation of ceRNAs that compete for shared miRNAs post-transcriptionally.…”
Section: Cervical Cancermentioning
confidence: 99%
See 3 more Smart Citations